SIFAT FISIK DAN MEKANIK BIOPLASTIK DARI PATI KULIT PISANG AMBON (Musa paradisiacal) DENGAN PLASTICIZER SORBITOL: Physical And Mechanical Properties of Bioplastic From Ambon Banana Skin Starch with Sorbitol Plasticizer - Endo Pebri Dani Putra; Elfa Susanti Thamrin (Universitas Darussalam Gontor, 2022)
Bioplastic is a solution to the large amount of plastic waste that causes problems for our environment today because it is difficult to degrade in nature. Bioplastic is a type of environmentally friendly plastic that can be decomposed naturally and made from renewable resources. The purpose of this study was to analyze the characteristics of the bioplastic film produced from Ambon banana peel starch and to obtain the best concentration of Ambon banana peel starch (Musa paradisiacal) to produce bioplastic films with sorbitol plasticizer. The method used in the manufacture of bioplastics is the solution casting method. The analysis carried out on the bioplastic film is physical properties in the form of measuring thickness, density, water absorption, and mechanical properties; tensile strength test, percent elongation, and Young's modulus. The results of the analysis of the data obtained indicate that the characteristics of the bioplastic films produced with different starch concentrations affect the thickness, density, water absorption, tensile strength, and Young's modulus. The best treatment based on the mechanical properties of the bioplastic film was the addition of 1 g of Ambon banana peel starch. The characteristics of Ambon banana starch bioplastic film with a thickness value of 0.31 mm, density 0.69 m/g3, 6.71% water absorption, 38.26 MPa tensile strength, 16.67% elongation percent, and 229.54 MPa young's modulus.